If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=6+h/2
We move all terms to the left:
5-(6+h/2)=0
We add all the numbers together, and all the variables
-(h/2+6)+5=0
We get rid of parentheses
-h/2-6+5=0
We multiply all the terms by the denominator
-h-6*2+5*2=0
We add all the numbers together, and all the variables
-1h-2=0
We move all terms containing h to the left, all other terms to the right
-h=2
h=2/-1
h=-2
| 9u=28+2u | | l+l+l=l+3l-10+l+3l-10 | | 40=x+20 | | 12x+66+6x-12=180 | | 0.3z=0.009 | | -2=2(-2+r) | | 6+2t-5=9t+1-6t | | 2^x2011+5x-7=0 | | 3|t+7|=33 | | -3.x=12 | | 2+1/2x+2/3x=1+5/6 | | 6d+8=10d+12 | | 15x-32+9x+68=180 | | 8x-2=3x+33 | | 850=40x+15x | | 16x+11=3x+50 | | 21/2x+2/3x=15/6 | | 12x-179=-x+162 | | 4x-27=12+x | | f(3)=5(3)-5 | | -1-15=n | | 2|x-1|=10 | | f(-2)=5(-2)-5 | | 3(5x+3)-7=7 | | -2=-2(a+2) | | 3/4x+4/5=3/10 | | -2.4=w/3+2.4 | | 3(x+5)=1+5(x-6) | | 2x^2-6x-2=4x-3 | | p/2+1=3 | | 9(x+10)+2=-8(x-2)-6 | | 12(t-4)+6t=6(3t+3)-10 |